(untitled) (Research, Society and Development, 2021)
Teacher education has been the subject of debates and profound reforms in Brazil and around the world. At this moment, we will be addressing the issues related to the challenges of this teacher education. This is a research carried out with teachers from a municipality in the interior of Maranhão that discusses the multiple challenges of teacher education, addressing the pros and cons of this profession. As a theoretical foundation, we are based on studies by Miguel Arroyo, Franco, Facci, Morin, Freire, among others. The methodology used was a bibliographical research and the analysis of the data collected through a questionnaire, were systematized according to the Content Analysis of Bardin. Studies on teacher training imply knowledge of the relationships that structure it, such as: considering the teacher as a subject and the school as a training space; analyze everyday situations at school; teacher training involves a continuous movement towards the development of this profession. It is in this sense that we see the need for teacher training to be strengthened at the base.